Creating apparent bipolarity as an elementary component of activity of Podemos = Kreowanie pozornej bipolarności jako elementarny komponent działalności Podemos - Górnicka, Weronika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this article is to analyze the specifics of the functioning of the party Podemos in the context of the phenomenon of bipolarity. It is assumed that the creation of the Spanish policy of political forces, based on two different groups - citizens and "caste" is a fundamental factor in determining the characteristics of a group and methods of its activities.
Keywords: apparent bipolarity; antagonism; agonism; Podemos; the Movement 15-M; pozorna bipolarność; antagonizm; agonizm; Ruch 15-M